IOT Based Intelligent System for Waste Management - Badadhe Komal R; Dahiwal Shital S (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
To make the cities greener, safer, and more efficient, Internet of Things (IoT) can play an important role. Improvement in safety and quality of life can be achieved by connecting devices, vehicles and infrastructure all around in a city. Best technological solutions can be achieved in smart cities by making different stakeholders to work to-gether. System integrators, network operators and technology providers have a role toplay in working with governments to enable smart solutions. But, building such solutions on an open, standards based communications platform that can be continuously used is a challenge. The Collection of waste is a very much needed municipal service that requires hugeexpenditures and execution of this operation is high-priced. The high pricing is due tothe various factors such as man power, navigation of vehicles, fuel, maintenances andenvironmental costs. The above factor necessitates the design, implementation and exe-cution of the intelligent smart bin for proper management of waste. This paper focusedon the implementation of an IoT based embedded system which integrates Radio Fre-quency Identification (RFID), Sensors, Arduino controller. This system provides a database of the information of bin status, amount of waste inthe bin, time of the collection of waste are transmitted to monitor and efficiently managethe waste collection strategies.